Partnership of state and business as a base of economic mechanism of formation and functioning of the «green» economy (Eurasian Journal of Ecology, 2016)
The article views theoretical and practical aspects of define the mechanism go to «green» economy, proposed approaches to formation of the concept of public-private partnership as a way of the effective implementation of the objectives of the «green» economy.
Keywords: Partnership; state; business; «green» economy; regional differentiation; subject of interest; subject-object analysis; economic mechanism.